2008
DOI: 10.1038/npp.2008.46
|View full text |Cite
|
Sign up to set email alerts
|

DHEA Lessens Depressive-Like Behavior via GABA-ergic Modulation of the Mesolimbic System

Abstract: Alterations in the levels of dehydroepiandrosterone (DHEA) in the brain can allosterically modulate g-aminobutyric-acid-type-A (GABA A R), N-methyl-D-aspartate (NMDAR), and Sigma-1 (s1R) receptors. In humans, DHEA has antidepressive effects; however, the mechanism is unknown. We examined whether alterations in DHEA also occur in an animal model of depression, the Flinders-sensitiveline (FSL) rats, with the intention of determining the brain site of DHEA action and its antidepressant mechanism. We discovered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 62 publications
1
32
0
6
Order By: Relevance
“…22,[28][29][30] Animal studies have revealed that DHEA-s administration improves depressive-like behavior, mediated by -aminobutyric acid receptors in the mesolimbic system. 31) In addition, anti-inflammatory and anti-oxidant properties of DHEA-s, along with various biological actions of DHEA-s in the brain, such as neurogenesis and inhibition of apoptosis, are possibly related to mechanisms against depression. 22) Supporting these findings, some previous studies reported lower DHEA-s levels in patients with depression than in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…22,[28][29][30] Animal studies have revealed that DHEA-s administration improves depressive-like behavior, mediated by -aminobutyric acid receptors in the mesolimbic system. 31) In addition, anti-inflammatory and anti-oxidant properties of DHEA-s, along with various biological actions of DHEA-s in the brain, such as neurogenesis and inhibition of apoptosis, are possibly related to mechanisms against depression. 22) Supporting these findings, some previous studies reported lower DHEA-s levels in patients with depression than in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…К сожалению, данные по активности ПОЛ у молодых животных со стандартным поведением в настоящей работе от-сутствуют. Однако наши ранние работы [15][16] и литературные данные [26][27][28] указывают на увели-чение интенсивности ПОЛ при старении. В ответ на острое стрессовое воздействие ак-тивность GR у молодых животных с депрессивно-подобным поведением проявляла лишь легкую тенденцию к увеличению, тогда как резко увели-чивалась у молодых животных со стандартным поведением.…”
Section: таблица 4 динамика концентрации тбк-активных продуктов в эрunclassified
“…В ответ на острое стрессовое воздействие ак-тивность GR у молодых животных с депрессивно-подобным поведением проявляла лишь легкую тенденцию к увеличению, тогда как резко увели-чивалась у молодых животных со стандартным поведением. Ранее нами также отмечалось уве-личение активности эритроцитарной GR у самок макак резус в ответ на аналогичное стрессовое воздействие, но в отсутствие деления живот-ных на определенные поведенческие типы [13,[15][16].…”
Section: таблица 4 динамика концентрации тбк-активных продуктов в эрunclassified
See 2 more Smart Citations